PROBLEMATIKA PEMBELAJARAN BAHASA ARAB MENGGUNAKAN APLIKASI WHATSAPP SELAMA PANDEMI COVID-19 PADA SISWA MADRASAH IBTIDA’IYAH DI KOTA BIMA - Ahmad Syagif (Prodi PGMI STIT Sunan Giri Bima, 2021)
This paper aims to identify the extent of the use of the WhatsApp application and the problems that accompany it when it is used in learning Arabic for students of Madrasah Ibtida'iyah in Bima City. With a qualitative approach and using research subjects from parents and students of Madrasah Ibtidaiyah in Bima City during the covid-19 pandemic. The data were collected through observation, interviews, and documentation. After going through the analysis process, it was found that the use of the WhatsApp application in learning Arabic at the Madrasah Ibtida'iyah level focuses more on mufradat and tarkib aspects and is more relevant for increasing maharah qira'ah and kitabah. In addition, there are problems of saturation, validity of assessments, integrity dilemmas, and technical constraints such as device specifications, finances, and inadequate assistance by teachers and parents.